Rola banków spółdzielczych w poszerzaniu dostępu rolników do kredytu w Polsce południowo-wschodniej - Kata, Ryszard (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The most important element of agriculture financial system in Poland are cooperative banks. Their part is particularly important in credit giving of dispersed agriculture, which is often beyond interest area of commercial banks. Large meaning of cooperative banks on agricultural credits market is a result of their strong position in rural environment as well as experience in financial service of agriculture. An essential element of their activity model is building and keeping permanent relation-ship with customers characteristic for local banks. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 120-127